Divergent experiences of U.S. veterans who did and did not complete trauma-focused therapies for PTSD: A national qualitative study of treatment dropout. (July 2022) - Kehle-Forbes, Shannon M.; Ackland, Princess E.; Spoont, Michele R.; Meis, Laura A.; Orazem, Robert J.; Lyon, Alexandra; Valenstein-Mah, Helen R.; Schnurr, Paula P.; Zickmund, Susan L.; Foa, Edna B.; Chard, Kathleen M.; Alpert, Elizabeth; et al.
Abstract: Prolonged Exposure (PE) and Cognitive Processing Therapy (CPT) are first-line treatments for posttraumatic stress disorder (PTSD) and have been disseminated throughout the U.S. Veterans Health Administration. Treatment non-completion is common and lessens clinical effectiveness; however, prior work has failed to identify factors consistently associated with non-completion. Semi-structured interviews were conducted with a national sample of veterans who recently completed ( n = 60) or did not complete ( n = 66) PE or CPT. Non-completer interviews focused on factors that contributed to veterans' decisions to drop out and efforts undertaken to complete PE/CPT. Completer interviews focused on challenges faced in completing treatment and facilitators of completion. Transcripts were coded using a mixed deductive/inductive approach; constant comparison was used to identify differences between completers and non-completers. Completers and non-completers differed in the extent of treatment-specific therapist support received, therapists' flexibility in treatment delivery, the type of encouragement offered by the care team and social supports, their interpretation of symptom worsening, the perceived impact of treatment on functioning, and the impact of stressors on their treatment engagement. Treatment-specific therapist support, more patient-centered and flexible treatment delivery, leveraging the full care team, and addressing functional concerns are potential targets for PE and CPT engagement interventions. Highlights: Completers and non-completers had many similar treatment experiences. Treatment-specific therapist support differentiated completers. Flexible, patient-centered delivery associated with completion. Interpretations of symptom worsening discriminated completers & non-completers. Full care team has a role in facilitating treatment completion.